Effects of the Coronavirus Disease 2019 Pandemic on Human Immunodeficiency Virus Services: Findings from 11 Sub-Saharan African Countries. (15th November 2021) - Harris, Tiffany G; Jaszi, Edward; Lamb, Matthew R; Laudari, Carlos A; Furtado, Maria Lúcia Mendes; Nijirazana, Bonaparte; Aimé, Ndayizeye; Loni Ekali, Gabriel; Ebiama Lifanda, Lifanda; Brou, Hermann; Ehui, Eboi; Malele Bazola, Faustin; et al.
Abstract: Background: Due to concerns about the effects of the coronavirus disease 2019 (COVID-19 pandemic on health services, we examined its effects on human immunodeficiency virus (HIV) services in sub-Saharan Africa. Methods: Quarterly data (Q1, 10/2019–12/2019; Q2, 1/2020–3/2020; Q3, 4/2020–6/2020; Q4, 7/2020–9/2020) from 1059 health facilities in 11 countries were analyzed and categorized by stringency of pandemic measures. We conducted a difference-in-differences assessment of HIV service changes from Q1–Q2 to Q3–Q4 by higher vs lower stringency. Results: There was a 3.3% decrease in the number HIV tested from Q2 to Q3 (572 845 to 553 780), with the number testing HIV-positive declining by 4.9% from Q2 to Q3. From Q3 to Q4, the number tested increased by 10.6% (612 646), with an increase of 8.8% (23 457) in the number testing HIV-positive with similar yield (3.8%). New antiretroviral therapy (ART) initiations declined by 9.8% from Q2 to Q3 but increased in Q4 by 9.8%. Across all quarters, the number on ART increased (Q1, 419 028 to Q4, 476 010). The number receiving viral load (VL) testing in the prior 12 months increased (Q1, 255 290 to Q4, 312 869). No decrease was noted in VL suppression (Q1, 87.5% to Q4, 90.1%). HIV testing ( P < .0001) and new ART initiations ( P = .001) were inversely associated with stringency. Conclusions: After initial declines, rebound was brisk, with increases noted in the number HIV tested, newly initiated or currently on ART, VL testing, and VL suppression throughout the period, demonstrating HIV program resilience in the face of the COVID-19 crisis. Abstract : While alarming predictions were made regarding potential impacts of the coronavirus disease 2019 (COVID-19) pandemic on human immunodeficiency virus services, few empiric data exist. Our findings demonstrate remarkable resilience. Lessons learned and how programs adapted can inform future responses.